PRODUCT DESIGN PRINCIPLES - Ștefan GHIMIȘI,; Dana NICULA (Fiabilitate şi Durabilitate)
Paper aims to present both the methodology for the design of a product and product design methods. It presents the theory of inventive problem solving (TRIZ), witch with its search concepts becomes an application of rules and laws from "experimental" concrete data abstraction . TRIZ role is to generate ideas carrier solution.